The Peptidic GHS-R antagonist [D-Lys(3)]GHRP-6 markedly improves adiposity and related metabolic abnormalities in a mouse model of postmenopausal obesity - Maletínská, L; Matyšková, R; Maixnerová, J; Sýkora, D; Pýchová, M; Spolcová, A; Blechová, M; Drápalová, J; Lacinová, Z; Haluzík, M; Zelezná, B (Molecular and cellular endocrinology, 2011)
It was demonstrated that estrogen deficiency and consuming high fat (HF) diet enhanced orexigenic activity of ghrelin. Therefore, we hypothesized that antagonizing of ghrelin action would attenuate food intake and body weight in mice obese both from ovariectomy (OVX) and feeding a HF diet. Ghrelin receptor antagonist [D-Lys(3)]GHRP-6 after seven days of subcutaneous treatment markedly decreased food intake in OVX mice fed both HF and standard diets; furthermore, it reduced body weight and blood glucose, insulin and leptin, and increased β-hydroxybutyrate level and uncoupling-protein-1 mRNA in brown adipose tissue. Pair-feeding revealed that effect of [D-Lys(3)]GHRP-6 was primary anorexigenic. Estrogen supplementation reduced anorexigenic effects of [D-Lys(3)]GHRP-6. OVX [D-Lys(3)]GHRP-6 treatment in mice on HF diet resulted in markedly increased circulating level and liver expression of a major metabolic regulator, fibroblast growth factor 21. Our data suggest that ghrelin antagonists could be especially beneficial in individuals with common obesity combined with estrogen deficiency.
Keywords: receptory ghrelinu; Models, Animal; Behavior, Animal; Male; Ovariectomy; adipozita; Obesity; Receptors, Ghrelin; ghrelin; přijímání potravy; Uncoupling Protein 1; estrogeny; postmenopauza; obezita; Diet, High-Fat; iontové kanály; PPAR alfa; mužské pohlaví; dieta s vysokým obsahem tuků; Eating; mitochondriální proteiny; PPAR alpha; Oligopeptides; Body Weight; Ion Channels; hnědá tuková tkáň; Mitochondrial Proteins; Postmenopause; Animals; lidé; ženské pohlaví; uncoupling protein 1; ovarektomie; Glucose Transporter Type 1; Humans; zvířata; pohybová aktivita; Adiposity; myši inbrední C57BL; Motor Activity; myši; chování zvířat; modely u zvířat; Mice, Inbred C57BL; Ghrelin; přenašeč glukosy typ 1; Estrogens; Female; Adipose Tissue, Brown; oligopeptidy; Mice; tělesná hmotnost